Telling it Straight: A Comparison of Selected English and Polish Idioms From the Semantic Field of Speaking - Szczepaniak, Renata; Adamska-Sałaciak, Arleta (Studia Anglica Posnaniensia, 2011)
This paper attempts to illustrate one way of achieving greater precision in presenting idiomatic equivalents by implementing the functionally-oriented methodological instrument devised by Dobrovol'skij and Piirainen (2005). A small-scale analysis along the three parameters of semantics, syntax and pragmatics is carried out with a view to identifying and explaining all cross-linguistic contrasts and similarities between selected English and Polish near-equivalent idioms from the semantic field of speaking. The empirical data of this study includes corpus evidence, apart from the available monolingual, bilingual and phraseological dictionaries. The resultant descriptions of the idiomatic expressions attest the validity of a functional approach to contrastive idiom analysis, which, unlike judgments based on the superficial properties of idioms (i.e. their lexical components, structure), reveals that differences in images will not always prevent idioms with similar actual meaning from being regarded as equivalents. On the other hand, closeness of underlying imagery does not guarantee identity with respect to all parameters of comparison (especially pragmatics).